2021
DOI: 10.4314/ahs.v21i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of NDM-1 and OXA-48 genes in Carbapenem Resistant Klebsiella pneumoniae clinical isolates in Kafrelsheikh, Egypt

Abstract: Background: The noteworthy spread of carbapenem-resistant K. pneumoniae (CR-KP) isolates represents a significant safety threat. Objective: Determination of the carbapenemase genes incidence among CR-KP clinical isolates in Kafrelsheikh, Egypt. Methods: A total of 230 K. pneumoniae isolates were recovered from four hospitals in Kafrelsheikh, Egypt. Susceptibility testing was conducted using Kirby-Bauer method and automated-Vitek2 system. CR-KP isolates were tested using modified Hodge test (MHT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
6
22
1
Order By: Relevance
“…The current study revealed that 76% of isolates were pan-drug resistant, 17% were extreme-drug resistant, and 7% were multidrug resistant. In addition, another study in Egypt detected that all 50 CRKP isolates were multidrug resistant (MDR) [ 24 ]. These values may be attributable to the absence of an appropriate antibiotic strategy used for VAP patients, ensuing long and improper use of antimicrobial agents, which has ultimately resulted in marked antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study revealed that 76% of isolates were pan-drug resistant, 17% were extreme-drug resistant, and 7% were multidrug resistant. In addition, another study in Egypt detected that all 50 CRKP isolates were multidrug resistant (MDR) [ 24 ]. These values may be attributable to the absence of an appropriate antibiotic strategy used for VAP patients, ensuing long and improper use of antimicrobial agents, which has ultimately resulted in marked antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Tawfick et al detected that bla NDM was the most prevalent genotype of carbapenemases by 68.88% (93/135). Furthermore, El-Domany et al stated that the incidence of bla NDM was 70.0% [ 24 , 28 ]. On the other hand, Ghaith et al, detected that the most prevalent carbapenemase gene was bla OXA-48 which was identified in 14/23 (60.8%) isolates followed by bla NDM , which was identified in 12/23 (52.2%) isolates [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…considered as rarely reported in Tunisia(Messaoudi et al 2017;Dziri et al 2019). In contrast, a coproduction of multiple types of carbapenemases by the same strain is more frequently reported in previous studies from several countries(Papagiannitsis et al 2017;Hamel et al 2020;El-Domany et al 2021). Recent studies from Egypte, Morocco and Thailand have reported that blaNDM-1+blaOXA-48 genes were one of the most prevalent carbapenemases genes co-existence among K. pneumoniae isolates with high incidence ranging from 24% to 48Á0%(Laolerd et al 2018;El-Domany et al 2021;Loqman et al 2021).…”
mentioning
confidence: 94%
“…PCR results for the commonly reported carbapenemase genes in Enterobacterales revealed that 80.8% of the isolates harbored carbapenemase genes, which is in concordance with another Egyptian study where carbapenemase genes were detected in 74% of the isolates. 30 The most prevalent gene was bla NDM (50%) followed by the bla OXA-48 (36.5%). This finding agrees with another study on Enterobacterales from Egyptian cancer patients, 31 but Raheel et al reported bla OXA-48 as the most common gene followed by bla NDM .…”
Section: Discussionmentioning
confidence: 98%